Cytotoxic and anti-inflammatory polyacetylenes from Tridax procumbens L - Tan Z.; Chen C.; Chen L.; Zeng J.; Zhang W.; Xu J.; He X.; Wang Y.
Herein, 17 previously undescribed polyacetylenes and 9 known ones were isolated from Tridax procumbens L. Their structures were identified using spectroscopic techniques (NMR, UV, IR, MS and optical rotation), the modified Mosher method, electronic circular dichroism (ECD) data and ECD calculation. The cytotoxicity of polyacetylenes on six human tumour cell lines (K562, K562/ADR, AGS, MGC-803, SPC-A-1 and MDA-MB-231) was evaluated. (3S,10R)-tridaxin B (2a), (3S,10S)-tridaxin B (2b) and tridaxin F (8) demonstrated substantial cytotoxic effects against the K562 cell line, with half-maximal inhibitory concentration (IC50) values of 2.62, 14.43 and 17.91 ?M, respectively. Cell and nucleus morphology assessments and Western blot analysis confirmed that the cytotoxicity of the three polyacetylenes on K562 cells was mediated through a dose-dependent apoptosis pathway. Furthermore, (3S,10R)-tridaxin A (1a) and tridaxin G (9) exhibited considerable inhibitory effects on lipopolysaccharide-stimulated nitric oxide production in RAW 264.7 macrophages, with IC50 values of 15.92 and 20.35 ?M, respectively. Further investigations revealed that 9 exerted anti-inflammatory activities by impeding the nuclear translocation of NF-?B and down-regulating the expression of pro-inflammatory factors, including those of iNOS, COX-2, IL-1? and IL-6, in a concentration-dependent manner. The study provides evidence that polyacetylenes from T. procumbens may serve as a potential source of anti-tumour or anti-inflammatory agents for treating related diseases. © 2024 Elsevier Ltd
Keywords: ANTI-INFLAMMATORY ACTIVITY; ASTERACEAE; COAT BUTTONS; CYTOTOXICITY; POLYACETYLENES; TRIDAX PROCUMBENS L